Effectiveness of Surgical Treatment in Traumatic Facial Paralysis. Issue 3 (29th May 2022) - Erkan, Zeynel Abidin; Erkan, Sanem Okşan; Tokucoglu, Figen
Abstract : Introduction: In the etiology of facial nerve palsy, trauma is the most important. Our aim was to present our experience gained by evaluating the surgical approaches we have used in extratemporal and intratemporal facial nerve injuries and their long-term results, also to contribute to the consensus that will be formed on this subject. Materials and Methods: Thirteen patients among 24 patients who underwent surgery with a diagnosis of traumatic facial paralysis were evaluated in this study. The clinical response of these patients to treatment was examined by classifying them according to the House-Brackmann classification in the preoperative and postoperative periods. Results: Of the 13 patients, 9 had fractures due to temporal bone trauma, and 4 had nerve damage in the extratemporal part of the facial nerve. in the treatment, facial nerve decompression was performed using the middle fossa approach in 9 patients with temporal bone fractures. in the 4 patients with extratemporal facial nerve injury, graft repair or primary suturing was performed. in the postoperative period, the stages of the patients were III or below in 12 patients (92%), and only 1 (8%) patient remained in stage IV. Discussion: When the postop conditions of the patients were examined according to House-Brackmann staging, it was observed that surgical treatment caused a significant improvement in the functions of the facial nerve. Conclusions: Our results showed that surgery was an effective treatment method in patients with indications for traumatic facial paralysis.